Epidemiology of cucumber mosaic cucumovirus isolates naturally infecting three solanaceous vegetable crops around Tirupati - and M. V. NAYUDU, G. KIRANMAI, P. SREENIVASULU (Indian Phytopathology, 2002)
During 1992-94, the incidence and progress of cucumber mosaic cucumovirus (CMV) in commercial aubergine, Capsicum and tomato crops around Tirupati, Chittoor district, Andhra Pradesh, India, during kharif and rabi seasons ranged from 9 to 21% in theyoung crops (10-15 days after transplanting) and increased to 74-86% as the crop aged. There was no significant difference in the incidence and progress of CMV in the 3 crops between the kharif and rabi seasons. Several other crop and weed